Analysis of Mathematical literacy Ability Viewed From Students’ Mathematics Self-concept Based on Gender Differences on IMPROVE Learning with PMRI Approach - Febriyana, Dyah; Suyitno, Hardi; Rochmad, Rochmad (Universitas Negeri Semarang, 2018)
This research was aimed to know the effectiveness of IMPROVE learning with PMRI approach and to describe student’s mathematical literacy ability based on their Mathematics self-concept and gender. The subjects of this study were the students of class VIII.4 as the experimental class and VIII.5 as control class. This research was conducted in SMP Negeri 2 Lubuklinggau South Sumatera in the academic year of 2017/2018. The result of this study showed that IMPROVE learning with PMRI approach is effective. In the aspect of the mathematical literacy process, female students with high mathematics self-concept is excellent in seven aspects, male students with high mathematics self-concept master in six aspects, women and men students with moderate mathematics self-concept master in the six aspects well, female students with low self-concept mathematics excellent in seven aspects, men with low mathematics self-concept mastered the five aspects well, and the last, female and male students with very low mathematics self-concept each mastered two aspects and five aspects.